Analisis Strategi Pemasaran Menggunakan Business Model Canvas (BMC) Pada Usaha Kerajinan Tangan Rotan Wickercane - Wiwit Syifa Istiqomah; Didit Purnomo (Universitas Muhammadiyah Surakarta, 2025)
The purpose of this business model canvas (BMC) analysis is to develop a well-developed business plan to improve the sustainability of Wickercane rattan craft company based in Kartasura, Sukoharjo. By using the Business Model Canvas (BMC) approach, this study attempts to examine the marketing strategy of Wickercane rattan craft company. Rattan crafts, such as wall decorations, hangers, wallets, and other items, are produced by Wickercane, a company with various domestic and international market potentials. Key components including client groups, value propositions, distribution channels, customer relationships, key resources, key partnerships, key activities, and cost structures are identified in this study using BMC.